New approach to improve COP and heat recovery in transcritical CO2 refrigeration system for milk processing application - Prosenjit Singha; Chayan Das; Mani Sankar Dasgupta; Souvik Bhattacharyya; Armin Hafner (Scientific Reports)
Abstract In hot climates, subcooling or after-cooling is an effective method to enhance the coefficient of performance (COP) of CO2 transcritical refrigeration system. This study investigates improvement of two contemporary subcooling arrangements: Integrated mechanical subcooling (IMS) and dedicated mechanical subcooling (DMS) and evaporative cooling arrangement to gascooler by introduction of gravity-fed evaporator in a dual evaporator parallel compression system suitable for milk processing. Using location-specific average meteorological data, the performance of the proposed systems is evaluated for Pune, India. Comparative analysis is conducted against a baseline transcritical CO2 system with flash gas bypass but lacking any subcooling arrangement. A considerable improvement in COP is observed when subcooling is combined with parallel compression. Incorporation of evaporative cooling with parallel compression yields 62.3% improvement in COP over the flash gas bypass system. However, heat recovery potential is considerably reduced by adopting evaporative cooling. Additionally, the study quantifies a potential reduction in water consumption of 45.6% over a system using flash gas bypass with an indirect evaporative cooling arrangement, and a reduction of 34.3% over a system employing parallel compression with a split gas cooler indirect evaporative cooling arrangement.